2021
DOI: 10.1155/2021/8810196
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Three Different Chemiluminescence Assays for Testing for SARS-CoV-2 Antibodies

Abstract: Several tests based on chemiluminescence immunoassay techniques have become available to test for SARS-CoV-2 antibodies. There is currently insufficient data on serology assay performance beyond 35 days after symptoms onset. We aimed to evaluate SARS-CoV-2 antibody tests on three widely used platforms. A chemiluminescent microparticle immunoassay (CMIA; Abbott Diagnostics, USA), a luminescence immunoassay (LIA; Diasorin, Italy), and an electrochemiluminescence immunoassay (ECLIA; Roche Diagnostics, Switzerland… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…In our study, 5 of nine PCV3 DB-1 inoculated piglets showed an obvious trend in the IgG antibody response. The indirect ELISA method used in our study based on PCV3 recombinant rCap-VLPs [ 23 , 30 ] might conserve the conformational epitopes and had the ability to detect IgG antibodies against the conformational epitope of the PCV3. Antibodies against rCap-VLPs of PCV3 that appeared in piglets with a specific immune status may be inflammatory factors that alert immune cells to respond to the viral infection; however, whether these antibodies can neutralize PCV3 requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, 5 of nine PCV3 DB-1 inoculated piglets showed an obvious trend in the IgG antibody response. The indirect ELISA method used in our study based on PCV3 recombinant rCap-VLPs [ 23 , 30 ] might conserve the conformational epitopes and had the ability to detect IgG antibodies against the conformational epitope of the PCV3. Antibodies against rCap-VLPs of PCV3 that appeared in piglets with a specific immune status may be inflammatory factors that alert immune cells to respond to the viral infection; however, whether these antibodies can neutralize PCV3 requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of patients exhibiting antibody loss was high in the present study, which may have implications for seroepidemiological investigations [ 36 ], especially those conducted recently, possibly leading to underestimated calculations of the prevalence of infection or even the susceptibility of the population to possible reinfection and thus compromising the success of current vaccination campaigns. Therefore, the use of tests with high sensitivity and specificity as chemiluminescent microparticle immunoassay, can enhance the accuracy and capacity of diagnosis of anti-SARS-CoV-2 antibodies [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The clinical performance of the different commercial assays, such as Abbott SARS-CoV-2 (N) IgG, DiaSorin SARS-CoV-2 S1/S2 IgG, and Roche Elecsys Anti-SARS-CoV-2 (N), have been investigated, and sensitivity greater than 80% and specificity greater than 95% 14 weeks after confirmed infection have been reported in hospitalized patients. Slightly lower sensitivity for antibodies has been observed in outpatient settings [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Roche Elecsys Anti-SARS-CoV-2 (S) is a quantitative assay that detects antibodies against the receptor-binding domain (RBD) with reported sensitivity of 84.0% 15–30 days post-PCR positivity, with no cross-reactivity leading to 100% specificity [ 47 ].…”
Section: Discussionmentioning
confidence: 99%